Mesenchymal Stromal Cell Therapy for Chronic Lung Allograft Dysfunction: Results of a First-in-Man Study. (1st February 2017) - Chambers, Daniel C.; Enever, Debra; Lawrence, Sharon; Sturm, Marian J.; Herrmann, Richard; Yerkovich, Stephanie; Musk, Michael; Hopkins, Peter M.A.
Abstract: Chronic lung transplant rejection (termed chronic lung allograft dysfunction [CLAD]) is the main impediment to long-term survival after lung transplantation. Bone marrow-derived mesenchymal stromal cells (MSCs) represent an attractive cell therapy in inflammatory diseases, including organ rejection, given their relative immune privilege and immunosuppressive and tolerogenic properties. Preclinical studies in models of obliterative bronchiolitis and human trials in graft versus host disease and renal transplantation suggest potential efficacy in CLAD. The purpose of this phase 1, single-arm study was to explore the feasibility and safety of intravenous delivery of allogeneic MSCs to patients with advanced CLAD. MSCs from unrelated donors were isolated from bone marrow, expanded and cryopreserved in a GMP-compliant facility. Patients had deteriorating CLAD and were bronchiolitis obliterans (BOS) grade ≥ 2 or grade 1 with risk factors for rapid progression. MSCs (2 x 10 6 cells per kilogram patient weight) were infused via a peripheral vein twice weekly for 2 weeks, with 52 weeks follow-up. Ten Patients (5 male, 8 bilateral, median [interquartile range] age 40 [30–59] years, 3 BOS2, 7 BOS3) participated. MSC treatment was well tolerated with all patients receiving the full dosing schedule without any procedure-related serious adverse events. The rate of decline in forced expiratory volume in one second slowed after the MSC infusions (120 ml/month preinfusion vs. 30 ml/month postinfusion, p  = .08). Two patients died at 152 and 270 days post-MSC treatment, both from progressive CLAD. In conclusion, infusion of allogeneic bone marrow-derived MSCs is feasible and safe even in patients with advanced CLAD.